A high efficacy and tunable white light‐emitting diode cluster with both color fidelity and nonvisual performances close to natural lights. Issue 6 (24th June 2020) - Li, Xinhao; Ding, Ke; Zhong, Ping; He, Guoxing
Abstract: A luminous efficacy model for a white light‐emitting diode (LED) cluster was developed, and five α‐opic efficacy ratios ( γ α, V s) of intrinsically photosensitive retinal ganglion cells were adopted in order to quantify its nonvisual performance relative to natural light. A tunable C/A/R LED cluster, which consists of the cyan LEDs with green phosphor excited by a blue LED, the amber LEDs with green and orange phosphors excited by same blue chip, and the red LEDs, was proposed by maximizing the average luminous efficacy at correlated color temperatures (CCTs) of 2700 to 6500 K under the condition of color fidelity index ( R f ) above 96 and five values of γ α, V of 0.95 to 1.05. The real tunable C/A/R LED cluster with a R f of 95 to 96, five values of γ α, V of 0.97 to 1.01, and a luminous efficacy of 114 to 120 lm/W at a CCT of 2670 to 6456 K were demonstrated. Furthermore, five values of γ α, V can be adjusted according to the distance from the Planckian or daylight locus on the CIE 1960 uv chromaticity diagram at different CCTs. Thus, the tunability of γ α, V value of the C/A/R LED cluster at a specific CCT could be applied to different requirements for nonvisual performance.